The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1757-899x/662/4/042016
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural land use change into tourism area in Lembang Sub-district, West Bandung Regency, West Java Province, Indonesia

Abstract: The research objective is to identify agricultural land use change and its impact on the community in Lembang Sub-district, West Bandung Regency. The research methods used were overlay technique and questionnaire distribution. Overlay technique was used to determine the location distribution of land use change. Land use maps of the year 2008 and 2015 were used for overlay analysis with geographic information system (GIS). Questionnaires were distributed to the residents of Lembang Sub District to gather inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A possible explanation of the phenomenon may be related to the rapid development of the northern part of the city during the last 10 years. The development activities created a region that provides better education, job opportunities, recreation, and standard of living that have encouraged temporary rural-urban immigration from established hot spots [ 70 ]. This result is supported by similar studies in Thailand [ 71 ] and Brazil [ 72 ] that showed a significant impact of human movement on the transmission of dengue in a local area.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation of the phenomenon may be related to the rapid development of the northern part of the city during the last 10 years. The development activities created a region that provides better education, job opportunities, recreation, and standard of living that have encouraged temporary rural-urban immigration from established hot spots [ 70 ]. This result is supported by similar studies in Thailand [ 71 ] and Brazil [ 72 ] that showed a significant impact of human movement on the transmission of dengue in a local area.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some built-up areas are also found in Cileunyi, Ngamprah, Cisarua, Parongpong, and Lembang District (Figure 2). The percentage of the built-up regions increased from 2010 (22.84%) to 2018 (27.73%) (Figure 3) due to various factors, such as the nice natural view [2], development of tourism activities [1,31], availability of good infrastructure (road) [6], urban expansion of Bandung City [9,10], and the development of industry and urban areas in West Bandung Regency [3].…”
Section: Distribution Of Land Cover Area and Temperature Class In Nbamentioning
confidence: 99%